A new cytotoxic carbazole alkaloid from Clausena excavata - Yap, Taufiq Yun Hin; Peh, Tian Hai; Ee, Gwendoline Cheng Lian; Rahmani, Mawardi; Md. Sukari, Mohd Aspollah; Ali, Abdul Manaf; Muse, Radzali (Taylor & Francis, 2007)
A new carbazole alkaloid, 3-carbomethoxy-2-hydroxy-7-methoxycarbazole, Clausine-TY (1),together with two known carbazole alkaloid, Clausine-H (2) and Clausine-B (3), were isolated from the ethyl acetate extract of the stem bark of the Malaysian Clausena excavata. The structures of these compounds were elucidated by spectroscopic analyses. The new carbazole alkaloid shows significant cytotoxicity against CEM-SS cell line.